Thermal Aging in Power Cables - How Thermal Stress Affects Aging in Underground 10 kV Cables - Engström, Petter (My University, 2026)
The electricity demand in Gothenburg is projected to increase over the next years. The current grid is pushed closer to its operational limits. For underground power cables, thermal stress is the leading cause of degradation, and to maintain a reliable grid, understanding the relationship between aging, current, and environment is crucial. The aim of this thesis is to design and analyze a model to quantify the thermal aging of the cable’s insulation for Gothenburg’s 10 kV grid. This work uses two cables, an older model with oil impregnated paper insulation, named FCJJ, and a modern one that uses cross-linked polyethylene insulation, called AXAL. With the simulation program COMSOL Multiphysics, partial differential equations (PDE) were solved for electromagnetic and thermal calculations. This was conducted for one, two, and three cable configurations. In addition, a sensitivity analysis was carried out to assess the effects of vital parameters, including varying loads during the different seasons, two scenarios of soil drying, which lead to lower thermal conductivity, and a scenario of higher load. The simulation data was integrated with the Arrhenius equations to calculate aging. The results show that while the composition of the one and two cables did not exceed their thermal rating for both cables, the three cables operated with smaller margins. As a result, this implies that mutual heating has an immense affect on the temperature of the cables and the surrounding soil. with this configuration the AXAL cables reached 81.1 ° C, which operates below the XLPE 90 ° C rated temperature. However, scenarios with drying soil and higher current exhibit the system’s potential vulnerability. With the worst case scenario where the surrounding soil dried up, the temperature spiked to over 125 ° C, the thermal aging factor reached 47 times the relative aging for which the cables were constructed. As a result, this would be catastrophic for the cable and the entire system, as it could lead to breakdown, warping of the conductors. Nevertheless, this scenario was deemed unrealistic due to the intervention of the grid’s monitoring systems and the mitigation of the current. However, it is theoretically possible to happen, which concludes that understanding the phenomenon is essential when designing and monitoring underground cables. The thesis illustrates that the three FCJJ and AXAL cable configurations can handle loads under normal conditions. However, thermal instability in underground power cables, cable placement, soil moisture, and load are major factors. These insights are vital when planning grid projects and implementing the dynamic cable rating.
Keywords: Rated temperature, thermal conductivity, thermal aging, mutual heating, XLPE, oil impregnated paper insulation, Arrhenius equation, COMSOL Multiphysics, 10 kV, power cable